TARGETS TO COMBAT OBESITY – AN REVIEW - MAHALAKSHMI.T; SUDHA RAMAIAH (International Journal of Pharma and Bio Sciences, 2013)
Obesity is a multifactorial, chronic disorder in most of the countries and becoming a global epidemic. In this review, various approaches namely increased thermogenesis, decreased or reduced fat absorption, modification of fat metabolism and reduction of food intake and their mechanism of action to combat obesity is discussed. The recent developments on these approaches are briefly given.